Influence of Solute Carrier Family 22 Member 1 (SLC22A1) Gene Polymorphism on Metformin Pharmacokinetics and HbA1c Levels: A Systematic Review - Pradana, A.D.; Kristin, E.; Nugrahaningsih, D.A.A.; Nugroho, A.K.; Pinzon, R.T. (Current Diabetes Reviews, 2024)
Background: Solute Carrier Family 22 Member 1 (SLC22A1, also known as OCT1) protein has a vital role in the metabolism of metformin, a first-line anti-diabetes medication. Genetic poly-morphism in SLC22A1 influences individual response to metformin. Objective: This review aims to compile the current knowledge about the effects of SLC22A1 genetic polymorphism on metformin pharmacokinetics and HbA1c levels. Methods: We followed the PRISMA 2020 standards to conduct a systematic review. We searched the publications for all appropriate evidence on the effects of SLC22A1 genetic polymorphism on metformin pharmacokinetics and HbA1c from January 2002 to December 2022. Results: Initial database searches identified 7,171 relevant studies. We reviewed 155 titles and abstracts after deleting duplicates. After applying inclusion and exclusion criteria, 23 studies remained. Conclusion: Three studies found that rs12208357, rs34059508, and G465R had a considerable impact (p < 0.05) on metformin pharmacokinetics, resulting in increased metformin plasma (Cmax), a higher active amount of drug in the blood (AUC), and lower volume of distribution (Vd) (p<0.05). SLC22A1 polymorphisms with effects on HbA1c include rs628031 (four of seven studies), rs622342 (four of six studies), rs594709 (one study), rs2297374, and rs1867351 (one of two studies), rs34130495 (one study), and rs11212617 (one study) (p < 0.05).
Keywords: pharmacokinetics